Temperature-dependent size effects on the strength of Ta and W micropillars. (15th January 2016) - Torrents Abad, Oscar; Wheeler, Jeffrey M.; Michler, Johann; Schneider, Andreas S.; Arzt, Eduard
Abstract: The strength of metals increases with decreasing sample size, a trend known as the size effect. In particular, focused ion beam-milled body-centered cubic (BCC) micropillars exhibit a size effect known to scale with the ratio of the test temperature to the critical temperature (Tc ) of the BCC metal, a measure of how much the yield stress is governed by the lattice resistance. In this paper, this effect is systematically studied by performing high-temperature compression tests on focused ion beam-manufactured Ta and W single crystal pillars ranging in diameter from 500 nm to 5 μm at temperatures up to 400 °C, and discussed in the context of bulk strength and size dependent stresses. Both metals show larger size effects at higher temperatures, reaching values that are in the range of FCC metals at temperatures near Tc . However, it is demonstrated that size effects can be considerably affected by material parameters such as dislocation density and lattice friction, as well as by the yield criterion used. Furthermore, for W, a change from uniform wavy deformation to localized deformation is observed with increasing temperature and pillar size, further indicating that the temperature ratio strongly influences the relative motion of screw and edge dislocations. Graphical abstract: